Potential use of green algae Caulerpa lentillifera as feed ingredient in the diet of Nile tilapia Oreochromis niloticus - Nadisa Theresia Putri; Dedi Jusadi; Mia Setiawati; Mas Tri Djoko Sunarno (Jurnal Akuakultur Indonesia)
ABSTRACT